Analysis and evaluation of temperature field and experiment for magnetorheological fluid testing devices. (April 2021) - Xiong, Hao; Luo, Yiping; Ji, Dongsheng; Ren, Hongjuan; Wei, Dan; Liu, Wentao
When a large amount of heat is produced during the operation of a MRF (magnetorheological fluid) testing device, the temperature of the device will increase, which will in turn affect the characteristics of the MRF. Exploring the temperature field characteristics of the MRF yield stress testing device is necessary to improve the accuracy of the device. In this study, first, the yield stress testing device is designed, and then its temperature field model, including enameled wire and assembly gap, is established. Second, simulation software is used to simulate the temperature field change. Finally, a test platform is developed to test the simulation results, especially for two factors, namely, thermal conductivity of the coil winding and assembly gap, which demonstrate considerable influence. Comprehensive thermal conductivity and assembly clearance are determined, and the optimum temperature field of the device for measuring yield stress is resulted.